Client based portable information system for general practitioners - Martinka, Tomáš; Barták, Lukáš; Szabó, Zoltán (Lékař a technika, 2008)
Medical applications, with their need for a huge amount of well-arranged information, should be the subject of a continuous improvement and should stay in the forefront of the development of information science. Unfortunately, even in recent times, in the age of rapid and accelerating development in the areas of the internet and mobile applications, there is still a very dated approach for the information systems solution. Our suggested solution improves on the lacks inherent in the current information systems for general practitioners and additionally adds utility to the user in the areas of portability and mobility of IS systems. Security of all criteria needed for the manipulation with sensitive data is obvious…
Keywords: Telemedicine; Medical Records; Information Systems; software; lidé; Physicians, Family; Computers, Handheld; Practice Management; telemedicína; Electronic Prescribing; rodinní lékaři; přístup pacientů ke zdravotnickým záznamům; mobilní telefon; chorobopisy; počítače do ruky; Cell Phone; Patient Access to Records; management lékařské praxe; elektronické předepisování; informační systémy; Software; Humans